Peran Kepemimpinan dalam Mewujudkan Good Governance Pendidikan Islam - Riza Kurnia; Saidina Saidina; Kasinyo Harto; Tutut Handayani (Journal of Innovative and Creativity, 2025)
Background: The dynamics of Islamic educational institution management in the contemporary era face complex challenges that demand leadership transformation based on accountable and transparent governance. Empirical phenomena indicate that management crises in Islamic educational institutions often stem from weak good governance practices, reflected in minimal accountability, transparency, and stakeholder participation in strategic decision-making. This situation is exacerbated by resistance to change, limited human resource competencies, and technological infrastructure gaps that hinder educational effectiveness. Purpose: This study aims to analyze the concept of leadership in Islamic education perspectives and its relevance to good governance principles, describe the implementation of good governance in contemporary Islamic educational institutions, identify leadership roles in realizing good governance, and analyze challenges faced by Islamic educational leaders in implementing good governance principles. Method: This research employs a qualitative method with a library research approach, utilizing systematic content analysis of primary sources including national and international reputable journal articles published between 2020-2025, and secondary sources comprising textbooks, research reports, and policy documents related to Islamic educational leadership and good governance. Results and Discussion: The findings confirm that Islamic leadership foundations based on amanah, al-'adalah, syura, and uswah hasanah principles demonstrate significant alignment with modern good governance principles encompassing transparency, accountability, participation, and responsiveness. Leadership functions as a transformative change agent in operationalizing good governance through strategic planning mechanisms, organizing, motivation, and systematic supervision. However, implementation faces internal challenges including limited HR competencies, organizational culture resistance, and stakeholder conflicts, as well as external challenges involving regulatory changes, funding limitations, and high societal expectations. Conclusion and Recommendation: The spiritual-transformational leadership model proves to be an effective contextual approach in integrating moral-spiritual dimensions with managerial aspects to create sustainable and responsive governance. It is recommended that Islamic educational leaders develop managerial and technological competencies through continuous training programs, prioritize transparent management information systems, build organizational culture supporting good governance values, and develop funding diversification strategies to enhance institutional competitiveness.